2010
DOI: 10.1080/02533952.2010.483826
|View full text |Cite
|
Sign up to set email alerts
|

The employment relationship in the domestic workspace in South Africa: beyond the apartheid legacy

Abstract: Employing more than one million people, domestic service is one of the largest sources of employment for black women in South Africa. In this article, we contend that, historically, the impact of apartheid has been to skew the analysis of employment relationships in domestic workspaces in South Africa so that the power asymmetry and exploitation that so characterise these relationships have been labelled an artefact of the racist apartheid regime and its legislation. By reviewing literature on domestic workers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…It does this by highlighting how the employers' lived experience affords them an experience of accessing opportunities to participate in occupations, but that that this may contribute to work conditions that contribute to experiences of occupational injustice for domestic workers. Although the domestic workers were not interviewed in this study, previous research has documented the limitations in domestic workers' work conditions 5,8,9,14,16 . It is thus postulated that there might be a relationship between the findings of the study presented in this paper and previous research describing the conditions of occupational injustice experienced by domestic workers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It does this by highlighting how the employers' lived experience affords them an experience of accessing opportunities to participate in occupations, but that that this may contribute to work conditions that contribute to experiences of occupational injustice for domestic workers. Although the domestic workers were not interviewed in this study, previous research has documented the limitations in domestic workers' work conditions 5,8,9,14,16 . It is thus postulated that there might be a relationship between the findings of the study presented in this paper and previous research describing the conditions of occupational injustice experienced by domestic workers.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in Brazil 15 and America 12 showed that the employers' way of asserting their power was rooted in social class, race and gender hierarchies operating in their relationships with their domestic workers. Likewise, research with domestic workers in South Africa showed that the relationship between the employers and domestic workers influenced how the employer used their positional power 16 . In America, Mendoza 12 showed that some ways in which employers exercised their positional power was in provision of food for and their delegation of work to the domestic worker.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Living wages here presupposes that domestic workers' salaries should be reviewed on a yearly basis based on the level of inflation just like wages of workers in other sectors. It is pertinent to point out why the conditions of employment of domestic workers have been very poor and deplorable in South Africa in the past and in this regard, du Preez et al (2010) writes that "historically, the impact of apartheid has been to skew the analysis of employment relationships in domestic workspaces in South Africa so that the power asymmetry and exploitation that so characterise these relationships have been labelled an artefact of the racist apartheid regime and its legislation." But the situation has now changed particularly with regard to wages with the promulgation of the sectoral determination which categorically prescribed living wages and in addition also prescribed the annual increases and revised wages, taking into consideration the cost of living.…”
Section: Implementing Minimum Wage and The Issue Of Cost Of Livingmentioning
confidence: 99%
“…In South Africa for an example, the sector employs more than one million people and it is one of the largest sources of employment for black women particularly the uneducated and the poor (du Preez et al 2010). Also, apart from being vulnerable, they are the most neglected sets of people in the employment relationships ( Kalleberg, 2009).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation